2020
DOI: 10.20944/preprints202003.0462.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Effect of Parenteral or Oral Iron Supplementation on Fatigue, Sleep, Quality of Life and Restless Legs Syndrome in Iron Deficient Blood Donors: A Secondary Analysis of the Ironwoman Rct

Abstract: Background: Besides anemia, iron deficiency may cause more subtle symptoms including those of the restless legs syndrome (RLS), the chronic fatigue syndrome (CFS) or sleeping disorders. Objective: The aim of this pre-planned secondary analysis was to compare the frequency and severity of symptoms associated with iron deficiency before and after (intravenous or oral) iron supplementation in iron deficient blood donors. Methods/Design: Prospective, randomized, controlled, single centre trial. (ClinicalTrials.gov… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…There is mounting evidence that rates of donor deferral due to low-Hb are considerably less in those taking iron supplements, both at the first donation visit and at subsequent donations. [44][45][46][47][48] Only providing donors with information about their (low) ferritin level does not seem to increase their iron intake. 15 The beneficial effects of iron supplementation may be counteracted by more frequent adverse events in donors who receive iron supplementation, which is likely to limit acceptability and compliance.…”
Section: Discussionmentioning
confidence: 99%
“…There is mounting evidence that rates of donor deferral due to low-Hb are considerably less in those taking iron supplements, both at the first donation visit and at subsequent donations. [44][45][46][47][48] Only providing donors with information about their (low) ferritin level does not seem to increase their iron intake. 15 The beneficial effects of iron supplementation may be counteracted by more frequent adverse events in donors who receive iron supplementation, which is likely to limit acceptability and compliance.…”
Section: Discussionmentioning
confidence: 99%
“…Pica was present in 2.2% of a mostly representative United States donor population and associated with low ferritin as well as RLS [9]. In several donor studies, an association between iron and RLS was not found [6,7,48] but one recent study reported improvements in RLS, sleep, and fatigue following use of exogenous iron [49]. An association with proton pump inhibitor medications and RLS was recently reported, even after controlling for iron status, emphasizing its multifactorial etiology [50].…”
Section: Impact Of Iron Deficiency On Blood Donor Healthmentioning
confidence: 99%
“…However, iron deficiency without anaemia has not been found to be associated with reduced self‐perceived health‐related quality of life in blood donors [8, 9]. Recently, iron supplementation was found to reduce iron deficiency‐related symptoms in non‐anaemic Swiss blood donors [10]. Iron levels of Finnish blood donor population are mostly affected by blood donation activity [11].…”
Section: Introductionmentioning
confidence: 99%